Leaf extracts of Clusia fluminensis Planck & Triana with allelopathic potential - Flávio Mauricio Perini; Josinei Rodrigues Filho; Alessandro Bermudes; Anderson Mariquito; Viviana Borges Corte; Hildegardo Seibert França (Revista Ceres)
ABSTRACT Our goal was to evaluate the bioherbicide effect of ethanol extract and its fractions of increasing polarity derived from the leaves of Clusia fluminensis, on the germination and initial growth of Lactuca sativa (lettuce) and Megathyrsus maximus (guinea grass), as well as their activity in the catalase, peroxidase, and superoxide dismutase enzymes. For the antioxidant capacity, the DPPH, ABTS, FRAP and phosphomolybdenum tests were used, in addition to the pigment content analysis. Chemical analyses were performed by quantification of total phenol, tannin, and flavonoid contents. The ethyl acetate fraction showed the best result, at concentration 0.75mg/mL, with less influence on lettuces seeds and greater influence on guinea grass seeds. In treatments with ethyl acetate fraction, there was a significant increase in the activity of the three enzymes in lettuce seeds, up to 67% in catalase. The catalase and dismutase enzyme activity decrease in 30% and 19%, respectively in guinea grass seeds. The presence of total phenols, tannins, and flavonoids on the ethyl acetate fraction allow a correlation to the most significant antioxidant activity by the ABTS, DPPH and FRAP assays. The results, therefore, suggest that the ethyl acetate fraction from leaves of C. fluminensis showed phytotoxic potential.